Sustainable synthesis of highly efficient sunlight-driven Ag embedded AgCl photocatalysts - Shen, Z.; Liu, B.; Pareek, V.; Wang, S.; Li, X.; Liu, Lihong; Liu, S. (Royal Society of Chemistry, 2015)
Plasmonic silver embedded silver chloride (Ag@AgCl) nano-photocatalysts were synthesized in a microbe-free aqueous lysogeny broth (Miller) solution, at room temperature with 5 min sunlight exposure. The nanohybrids were formed by in situ photoreduction and photo-accelerated ripening of AgCl colloids, promoted by the attached biomolecular ligands. Compared with commercial TiO2, the biogenic Ag@AgCl nanocomposites demonstrate higher photocatalytic activity towards decomposition of organic dye solution under solar light with excellent photocatalytic stability.